EKSPLORASI KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS V DALAM MENYELESAIKAN SOAL CERITA MELALUI IMPLEMENTASI MODEL PROJECT BASED LEARNING - Etika Rindu Wulansari; Fulusia Nurmawati; Muhammad Aunur Rofiq (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Mathematical problem-solving skills when dealing with word problems remain a major obstacle for elementary school students, particularly in analyzing issues, developing action plans, and re-verifying final findings. This study aims to describe the mathematical problem-solving skills of fifth-grade students in solving word problems through the application of the Project Based Learning (PjBL) model, while identifying patterns of students' cognitive processes based on problem-solving criteria. The study applied a qualitative method with an exploratory descriptive design carried out in fifth-grade students of SDN 2 Bogorejo in the second half of the 2025/2026 academic year. Subjects were selected purposively following the diversity of students' mathematical problem-solving abilities. Data collection methods included observation, interviews, word problem tests, and document reviews, with data validation through source and method triangulation. Data processing followed the steps of data reduction, data display, and conclusions based on the Miles and Huberman model. The uniqueness of this study lies in the detailed exploration of elementary school students' mathematical problem-solving skills through the integration of PjBL connected with a structured problem-solving sequence in a story problem situation that is relevant to reality. Research findings indicate that PjBL effectively maps the dynamics of students' thinking at each problem-solving stage. High-achieving students successfully decompose problems sequentially, while the medium- and low-achieving groups still struggle during the planning and assessment phases. Consequently, the use of PjBL fosters dynamic participation, teamwork, and strengthens students' understanding of the material and their ability to solve mathematical problems in a more context-based manner.